Are Immigrants’ Pay and Benefits Satisfaction Different than Canadian-born? - Chowhan, James; Zeytinoglu, Isik; Cooke, Gordon (Relations industrielles / Industrial Relations, 2012)
SummaryThis study contributes to the emerging literature on immigrants’ life, job, and pay satisfaction by focusing on a relatively understudied aspect of the immigrant experience – satisfaction with pay and benefits. The purpose of the study is to first examine whether there are differences in satisfaction with pay and benefits between Canadian-born and immigrant workers, and if so, to then examine factors associated with immigrants’ pay and benefits satisfaction using discrepancy and equity theoretical frameworks. Immigrants are examined in four cohorts based on the year of arrival. We use Statistics Canada’s 2005 Workplace and Employee Survey (WES), which is a large Canadian dataset containing responses from both employers and employees enabling us to control for individual and workplace heterogeneity. Both descriptive and multivariate regression results found that, with the exception of the pre-1965 cohort, all immigrant cohorts report significantly lower pay and benefit satisfaction compared to Canadian-born workers. Further, we find that for Canadian-born workers, external and internal referents, non-wage benefits, and pay-for-performance are positively related to pay and benefit satisfaction, whereas pay-for-output is important for the 1986 to 1995 and 1996 to 2005 immigrant cohorts.We conclude that the lack of consistency in the factors contributing to pay and benefits satisfaction across Canadian-born and immigrant groups suggests that the theories and traditional models for pay and benefit satisfaction may not be as relevant when studying immigrants. We recommend that further studies of a qualitative nature tease out factors associated with immigrants’ pay and benefits satisfaction and contribute to the refinement of existing theories. The results can also assist human resource managers and government policy-makers to facilitate more successful integration and retention of immigrants.